WORKSHOP PERANCANGAN AUGMENTED REALITY SEDERHANA UNTUK MENJUNJANG PEMBELAJARAN BIOLOGI DI SMK N 8 BATAM - Ellbert Hutabri; Nanda Jarti; Robby Satria; Nurma Dhona Handayani; Anggia Dasa Putri (ASOSIASI IDEBAHASA KEPRI, 2023)
Most community activities can be carried out via smartphones, including learning activities carried out remotely. However, not all students are able to use smartphones as learning aids, most of the students use them only for entertainment in the form of accessing social media, live streaming and playing games. This activity results in students being away from learning, especially when outside of school. In addition, the teacher also does not have specific learning media in accordance with the material to be taught at school, so that the use of this tool is very minimal for learning activities. In order for the use of this smartphone to be more positive among students, it is necessary to provide workshops that can increase students' interest in learning, one of which is with augmented reality, namely technology that combines virtual objects with the real world. Through this technology, students will be taught to design 3-dimensional objects and implement them into learning. It is hoped that by increasing students' knowledge of augmented reality technology, the use of smartphones will become more positive and can improve the quality of student learning. The implementation of this service uses an inquiry and performance model where students are given material and immediately practice the material being taught, it is hoped that at the last meeting students can complete several 3-dimensional objects and apply them in learning.